Investigations of martensitic, thermodynamics, elastic, electronic, magnetic, thermal and thermoelectric properties of Co2FeZ Heusler alloys (Z=Si; Ge; Al; Ga): a first principle study. (3rd June 2022) - Raïâ, M. Y.; Masrour, R.; Jabar, A.; Hamedoun, M.; Rezzouk, A.; Hourmatallah, A.; Benzakour, N.; Bouslykhane, K.; Kharbach, J.
Abstract : In this study, the first-principle calculations using FPLAPW based on density functional theory, have been employed to examine and deeply understand the martensitic, thermodynamics, elastic, electronic, magnetic, thermal and thermoelectric properties of full-Heusler Co2 FeZ in the L 21 phase. The fundamental physical properties such as lattice parameter, bulk modulus, anisotropy factor, Poisson's ratio, elastic constants, and Young's modulus are obtained and then compared with the theoretical and experimental results. Subsequently, Debye temperature, heat capacity, entropy, thermal expansion coefficient and Grüneisen parameter are also evaluated over the temperature range of 0–1500 K. The band structures and the density of states curves are presented for all alloys intended to interpret the electronic and magnetic stabilities of Co2 FeZ Heusler compounds in the L 21 phase. Additionally, the Seebeck coefficient, electrical conductivity, electronic thermal conductivity, and power factor of these systems have been studied as a function of the temperature and chemical potential. GRAPHICAL ABSTRACT: UF0001